Disruption of Bmal1 Impairs Blood–Brain Barrier Integrity via Pericyte Dysfunction - Nakazato, Ryota (J Neurosci, 2017)
Circadian rhythm disturbances are well established in neurological diseases. However, how these disruptions cause homeostatic imbalances remains poorly understood. Brain and muscle aryl hydrocarbon receptor nuclear translocator-like protein 1 (Bmal1) is a major circadian clock transcriptional activator, and Bmal1 deficiency in male Bmal1(nestin)(−/−) mice induced marked astroglial activation without affecting the number of astrocytes in the brain and spinal cord. Bmal1 deletion caused blood–brain barrier (BBB) hyperpermeability with an age-dependent loss of pericyte coverage of blood vessels in the brain. Using Nestin-green fluorescent protein (GFP) transgenic mice, we determined that pericytes are Nestin-GFP(+) in the adult brain. Bmal1 deletion caused Nestin-GFP(+) pericyte dysfunction, including the downregulation of platelet-derived growth factor receptor β (PDGFRβ), a protein necessary for maintaining BBB integrity. Knockdown of Bmal1 downregulated PDGFRβ transcription in the brain pericyte cell line. Thus, the circadian clock component Bmal1 maintains BBB integrity via regulating pericytes. SIGNIFICANCE STATEMENT Circadian rhythm disturbances may play a role in neurodegenerative disorders, such as Alzheimer's disease. Our results revealed that one of the circadian clock components maintains the integrity of the blood–brain barrier (BBB) by regulating vascular-embedded pericytes. These cells were recently identified as a vital component for the control of BBB permeability and cerebral blood flow. Our present study demonstrates the involvement of circadian clock component Bmal1 in BBB homeostasis and highlights the role of Bmal1 dysfunction in multiple neurological diseases.